Rational Design of Self-Emulsifying Pellet Formulation of Thymol: Technology Development Guided by Molecular-Level Structure Characterization and Ex Vivo Testing - Macku, Jan; Kubova, Katerina; Urbanova, Martina; Muselik, Jan; Franc, Ales; Koutna, Gabriela; Pavelkova, Miroslava; Vetchy, David; Masek, Josef; Maskova, Eliska; Brus, Jiri (Pharmaceutics, 2022)
The growing need for processing natural lipophilic and often volatile substances such as thymol, a promising candidate for topical treatment of intestinal mucosa, led us to the utilization of solid-state nuclear magnetic resonance (ss-NMR) spectroscopy for the rational design of enteric pellets with a thymol self-emulsifying system (SES). The SES (triacylglycerol, Labrasol®, and propylene glycol) provided a stable o/w emulsion with particle size between 1 and 7 µm. The ex vivo experiment confirmed the SES mucosal permeation and thymol delivery to enterocytes. Pellets W90 (MCC, Neusilin®US2, chitosan) were prepared using distilled water (90 g) by the M1–M3 extrusion/spheronisation methods varying in steps number and/or cumulative time. The pellets (705–740 µm) showed mostly comparable properties—zero friability, low intraparticular porosity (0–0.71%), and relatively high density (1.43–1.45%). They exhibited similar thymol release for 6 h (burst effect in 15th min ca. 60%), but its content increased (30–39.6 mg/g) with a shorter process time. The M3-W90 fluid-bed coated pellets (Eudragit®L) prevented undesirable thymol release in stomach conditions (<10% for 3 h). A detailed, ss-NMR investigation revealed structural differences across samples prepared by M1–M3 methods concerning system stability and internal interactions. The suggested formulation and methodology are promising for other lipophilic volatiles in treating intestinal diseases.